活动理论视角下的来华留学生汉语学习动机研究 - Yijie Wang; Shuang Zhang (Journal of Maobi, 2025)
This paper, based on activity theory and adopting a questionnaire survey and semi-structured interviews, investigated the features and influencing factors of Chinese language learning motivation among six international students learning Chinese in a local key university located in central China. Results revealed that the participants displayed a medium to high level of Chinese language learning motivation; and that their Chinese language learning motivation was influenced by five socio-cultural factors, including subject-related factors (language learning planning awareness, strategies, and interest), mediational tools (textbook difficulty and teaching facilities), rule-related factors (graduation stress and exams), learning communities (teachers and peers), and labor of division factors (teacher-student relationship, peer relationship). These findings offer implications for improving Chinese language teaching and learning efficiency to international Chinese language learners.